Estudio exploratorio del efecto de la saturación en el ensayo de California Bearing Ratio (CBR) de campo y laboratorio en el diseño de estructura de pavimento - Bustillos-Álvarez, William (Instituto Tecnológico de Costa Rica, 2010)
province of Cartago. It is to determine the effect of soil saturation, due to the precipitation that presents the site, California Bearing Ratio by laboratory and field tests. Also, through dampness models are determined for each month of the year for a rainy scene, designing the structure of the road for a laboratory CBR, which is compared by the probabilistic design associated with the climatic conditions of the place. Through laboratory testing is done to establish the relationship between CBR value and the change of soil saturation, in addition undertakes graphs that determine the behavior of CBR depending on the dry density and degree of saturation. Manage to evaluate the soil of the subgrade through the field CBR test, where the expected results are not satisfactory. Be evaluated the performance in terms of performance and productivity, to compare the procedures of the laboratory tests and field. It was determined that the climatic effect for the design of the pavement structure for the particular road has an effect on the conventional design, and established that the structure is over designed, where the economic impact of design.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Suelo; Diseño; Probabilidad; Pavimento; Humedad